جمالية الوصف في رثائية أبي تمام لابن حميد الطوسي (Comprehensive Journal of Science, 2026)
This study aims to analyze Abu Tammam 's Elegy for Ibn Hamid al-Tusi, which is considered one of the enduring masterpieces of lamentation in Arabic literature due to its profound meanings, noble themes, and cohesive structure. It is undoubtedly a sincere and remarkable artistic expression, born from the wounded self that overflows with pain due to the loss of a loved one.This is where my choice to analyze this elegy comes from, employing various methodological tools through an integrative approach that allows the researcher to engage with the text and highlight its artistic and stylistic aesthetics from different angles. Although the poem is a cohesive unit, I attempted to facilitate its study by dividing it into five sections based on its thematic structure. My aim is to achieve a general aesthetic vision that showcases the beauty and creativity in Abu Tammam's descriptions through the diverse stylistic techniques he employed in crafting this elegy.I began with the first section, highlighting the beauty of the introduction for its uniqueness and strangeness in the initial phase, which captures the recipient's attention and clearly reflects the features of the tragedy, the wounded self, and the magnitude of the loss. I then moved to analyze the second section, illustrating how the poet skillfully described the suffering of the poor and needy following Ibn Hamid Al-Tusi 's quotation, employing a beautiful artistic style based on vivid imagery and rhythmic repetition arising from phonetic harmony.Next, I specified how the poet transitioned smoothly to the third section, continuing the description of Almarthy’s bravery, showcasing his heroism through the remarkable imagery techniques he used in this section, celebrating his illustrious victories in a passionate and vigorous language. Subsequently, I examined the fourth section, which the poet dedicated to describing Ibn Hamid's qualities and enumerating the noble human values that characterized Almarthy, employing a style based on repetition, contrast, and comparison between the past and the present.In the fifth section, I clarified how the poet acknowledged the inevitability of fate, portraying the scene of bidding farewell of Almarthy in the most eloquent expressions of mourning, conveyed in a philosophical and vivid language grounded in metaphor and subtle symbolism. Finally, I concluded with a summary of the research and a bibliography of sources and references.